Drying Kinetics and Modelling of Convective Drying of Kedondong Fruit - Ee, C. T.; Khaw, Y. J.; Hii, C. L.; Chiang, C. L.; Djaeni, M. (ASEAN Journal of Chemical Engineering, 2021)
Kedondong is an underutilized fruit cultivated in a small scale in Malaysia and it contains nutrients that can be preserved through drying. The dried product can be sold as a premium fruit snack that could generate revenue for the producer. We studied the drying of peeled and unpeeled kedondong fruits using hot air (60-80°C). This study aims to investigate the drying kinetics (drying rates and effective diffusivities) of kedondong fruits and model the drying curves using thin layer models. Ten thin layer models were employed and solved using non-linear regression. Drying kinetics showed that only falling rate periods were observed, which implied that internal diffusion was the dominant mechanism for moisture release. Mathematical models showed that Modified Hii et al. (I) and (II) models were able to predict the drying curve well with the highest R2 (0.9992-0.9999), the lowest RMSE (8.0 x 10-4 - 2.5 x 10-3) and the lowest χ2 (4.0 ×10-5 - 2.0 x 10-4). Peeled samples showed higher effective diffusivities (average 3.2 x 10-11 m2/s) than unpeeled samples (average 2.7 x 10-11 m2/s). The activation energy was lower in peeled samples (25.8 kJ/mol) as moisture diffusion could occur more easily than unpeeled samples (32.1 kJ/mol). Results from this study provide kinetic information that can be used in scaling up of dryer and optimizing dryer performances.